Analysis of rumen contents and ocular fluid for toxic alkaloids from goats and cows dosed larkspur (Delphinium barbeyi), lupine (Lupinus leucophyllus), and death camas (Zigadenus paniculatus). (March 2020) - Lee, Stephen T.; Welch, Kevin D.; Stonecipher, Clinton A.; Cook, Daniel; Gardner, Dale R.; Pfister, James A.
Abstract: Larkspurs, lupines, and death camas can be acutely toxic to livestock and are serious poisonous plant problems in western North America. The toxicity of these plants depends on the composition and concentrations of the toxic alkaloids in the plants. In this study, goats and cows were dosed sub-lethal doses of larkspur, lupine, and death camas. Rumen contents and ocular fluid samples were collected, and simple extraction, sample preparation, and analytical methods were developed for the detection of toxic alkaloids in the rumen contents and ocular fluid samples. Toxic alkaloids were detected in the rumen contents and ocular fluid samples from the goats and cows dosed larkspur, lupine, and death camas. In addition, results from a case report where rumen contents were analyzed from a steer that was suspected to have died due to larkspur are reported. This demonstrates the utility of the methods described for the diagnosis of acute plant poisonings. Highlights: Diagnosing plant poisonings in livestock is challenging. Analytical methods for the detection of toxic plant alkaloids from the rumen contents and ocular fluid are presented. This is the first report of the detection of plant alkaloids in the ocular fluid of ruminants. Results of analysis of rumen contents from a steer that was suspected to have died due to larkspur are reported.